A language of loyalty?: oaths and their roles in late antiquity - Wuk, Michael (2020)
This thesis investigates the common social practice of taking oaths in Late Antiquity, broadly defined as the third to sixth centuries CE. An oath in antiquity was a sworn undertaking to which an individual was bound by the threat of supernatural retribution. Modern scholars therefore generally view oath-taking as a means of inducing members of society to fulfil their commitments. However, as the practice could not always be relied upon to ensure that individuals maintained their promises, there is a tendency in the scholarship to disregard oath-taking as merely symbolic in significance or simply ineffective. The following discussion argues that even if the intended purpose of taking these oaths was not always realised, the practice still had a number of uses.